Comparison of profitability proportions before and after the implementation of corporate governance in companies listed in Tehran Stock Exchange - Reza Golestani; Reza Fallah (Dutch Journal of Finance and Management, 2019)
The aim of this study was to compare the profitability proportions in companies before and after the use of corporate governance in the companies listed in Tehran Stock Exchange. The research method was descriptive and causal-comparative. The population was all the accepted companies in Tehran Stock Exchange (cars and car fragments, petrochemicals, petroleum products, cement, pharmaceutical, home and sugar appliances) between years of 2010 and 2014 that 82 companies were selected based on Morgan table as a sample. Data was analyzed using independent t-test. Results showed that the average ratio of gross profit to total assets (ROI) in companies after the application of corporate governance had no significant difference with an average ratio of gross profit to total assets (ROI) before the implementation of corporate governance. There was no significant difference between the average ratios of net income to equity (ROE) in companies after the application of corporate governance and net income to equity (ROE) in companies before the application of corporate governance. The average ratio of net profit to total assets (ROA) in companies after the application of corporate governance and average ratio of net profit to total assets (ROA) in companies before the application of corporate governance in companies did not significantly differ from each other. Other results showed that the average ratio of gross profit to total assets (ROI) in companies that used corporate governance had no statistically significant difference with an average ratio of gross profit to total assets (ROI) in companies that did not use corporate governance.
Keywords: 650; corporate governance; auditing; profit